Impact of Disinvestment on Financial Performance of Selected Public Sector Undertakings - Singh, Sultan; Bansal, Monica; Sukhija, Sunita (Indian Journal of Finance, 2009)
The main idea behind the disinvestments is realizing large amount of public resources locked up in non-strategic Public Sector Enterprises (PSEs) reemployment in area that are much higher on social priority such as basic health family welfare, primary education and social infrastructure. Disinvestments is initiated for reducing the public debt that is threatening to assume unmanageable proportion and transferring the commercial risk to which the taxpayer money locked up in public sector is exposed to the private sector is willing and able to step in the money that is deployed in the PSEs is really the public money and is exposed to an entirely avoidable and needless risk in most cases. The main objective of research is to study the impact of disinvestments on liquidity and long term solvency position of selected companies. It has been observed from the study that the database inadequacy is major hindrance toward the proper disinvestment. There is indeed a need to create a database, which covers information about industry, its functioning, value in India and abroad. Disinvestments need not and should not be regarded as a case of selling family silver. The original investments where made by the government out of its receipts.